Expatriate adjustment: Validating multicultural personality trait among self-initiated academic expatriates - Halim, Haslina (Elsevier Ltd., 2014)
This study looks at the adjustment of self initiated academic expatriates working at one of the public universities in Malaysia.The main aim of the research is to investigate the relationship between Multicultural Personality Questionnaire (MPQ) and the expatriate’s personal, professional and social adjustment.The MPQ consists of five dimensions - cultural empathy, openmindedness,social initiative, emotional stability and flexibility.One-hundred and one questionnaires were distributed to selfinitiated academic expatriates attached to various departments at the university. Results show that the MPQ predicts all three types of adjustment.Apart from the results, the discussions and limitations of the study are also presented in the paper.